Interaksi Kaum Sufi dengan Ahli Hadis: Melacak Akar Persinggungan Tasawuf dan Hadis - Arafat, Ahmad Tajuddin (UIN Walisongo Semarang, 2017)
This article examines the root of intersection between the study of Sufism and Hadith through the interaction between Sufis with the Hadis Transmitters (Ahl al-Hadis). A historical approach used in this research. The result founded that some early Sufis identified as active and credible transmitters of Hadis. Early Sufis generations already applied the exoteric views or irfani perspective toward understanding the Hadis. This view is a pillar for them to get the significance of the Prophetic traditions. It stated that early Sufis make the Prophet attitude as an ideal model for them. The research also founded that the Sufi’s interactions with the Transmitters are considered as a dialogical interaction between them. These interactions historically confirmed in the middle of the second century of hijriyah, for example, Ibnu Mubarak (118 H.), and the third century of hijriyah, al-Muhasibi (243 H) and Zun an-Nun al-Misri (245 H).* * *Artikel ini mengkaji akar persinggungan antara kajian Tasawuf dan Hadis melalui pola interaksi para Sufi dengan perawi Hadis (Ahl al-Hadis). Penelitian ini menggunakan pendekatan historis. Hasil penelitian menunjukkan bahwa ada beberapa sufi awal yang diidentifikasi sebagai perawi aktif dan kredibel dari Hadis. Sufi generasi awal sudah menerapkan pandangan eksoteris atau perspektif irfani terhadap pemahaman Hadis. Pandangan ini merupakan hal yang penting bagi mereka untuk mendapatkan hakikat makna hadis Nabi. Sufi awal selalu menjadikan Nabi sebagai model ideal untuk mereka. Gambaran interaksi Sufi dengan perawi dianggap sebagai interaksi dialogis antara keduanya. Interaksi ini secara historis terjadi pada pertengahan abad kedua hijriyah, terutama di zaman Ibnu Mubarak (118 H.), dan pada abad ketiga hijriyah, di era al-Muhasibi (243 H) dan Zun an-Nun al-Misri (245 H).